INCUBADORA DE ECONOMIA SOLIDÁRIA E DESENVOLVIMENTO REGIONAL SUSTENTÁVEL - LECHAT, NOËLLE; BARCELOS, ERONITA; BASSO, LAURI; RASIA, PEDRO; CAMPOS, ÍRIS; GOERCK, CAROLINE; LEMES, FÁBIO; ROTILI, ANA; SCARIOT, NADIA; ZIMMERMANN, IEDA; et al. (Salão do Conhecimento, 2013)
Resumo